Design and evaluation of convolutional neural network for detection of Alzheimer’s disease using MRI data - Mahbub, Riasat; Azim, Muhammad Anwarul; Reza, Khondaker Masfiq; Mahee, Md Nafiz Ishtiaque; MD. Zahidul Islam Sanjid (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.